Asymbiotic in vitro seed germination, in vitro seedling development, and ex vitro acclimatization of Spiranthes. (1st October 2022) - Zale, Peter J.; Clayton, Ashley; Nix, John; Taylor, Matt
Abstract: Premise: Reproducible seed propagation and production protocols were developed for Spiranthes and related taxa to facilitate ex situ conservation practices. Methods and Results: Spiranthes seeds were scarified for 3‐ and 10‐min intervals in 10% sodium hypochlorite solution, then cultured on three seed germination media. After germination, seedlings were given one of the three photoperiod treatments, and then planted in one of four greenhouse substrates. Seed germination ranged from 0% to 90% and occurred on all three media only after the 3‐min scarification. Seedlings in the 24/0‐h light/dark and 16/8‐h light/dark photoperiods on P723 medium had significantly higher fresh weight than those in the dark treatment group. Ex vitro survival ranged from 55% to 95% across substrates. Conclusions: Results show that Spiranthes seeds are damaged by extended chemical scarification, are adaptable to a variety of culture media, and require light for optimal development. Further experimentation showed that the propagation protocols described here can be applied broadly within the genus.